Investigation on the bond-slip behavior of recycled aggregate concrete-filled steel tube with studs - Gehao Cai; Bing Sun; Sheng Zeng; Peng Yang; Jie Zhang (PLoS ONE, 2025)
This study investigates the influence of built-in studs on the bond behavior in recycled aggregate concrete-filled steel tube (RACFST) composite structures through push-out experiments. The effects of stud number, position, and rows on RACFST bond strength and steel tube surface strain are systematically analyzed. Furthermore, the bond-slip behavior evolution mechanism is examined, and a constitutive equation is established. A novel interfacial modeling approach is developed via secondary development of ABAQUS software to comprehensively simulate RACFST interfacial bond-slip behavior. The results demonstrate that insufficient stud quantity compromises interface integrity, reducing bond strength, while increased stud count enhances composite stiffness and bond performance. Studs positioned nearer the free end extend the natural bond length participating in shear resistance, thereby improving bond strength. Internal studs promote stress redistribution within the composite structure, significantly improving collaborative performance. The proposed constitutive equation shows good agreement with experimental results, and the developed interface program accurately captures bond-slip curve trends. These findings facilitate RACFST applications and provide guidance for shear stud arrangement in RACFST structures.